Adhesion Improvement of Hydroxyapatite Layer on Ti-6Al-4V ELI with the Contribution of PVA and Zirconium Oxide for Biomedical Applications - Ardhy, Sanny; Islahuddin, Islahuddin (Department of Mechanical Engineering, Universitas Andalas, 2024)
Ti-6Al-4V Extra Low Interstitial (ELI) is one of the most widely used titanium alloys for orthopedic implants. However, its drawback is that titanium has less bioactive properties. Therefore, Ti-6Al-4V ELI needs to be coated with hydroxyapatite (HA) to achieve good osseointegration in the human body. Nevertheless, several studies have shown that there are still cracks found on the HA surface layer. This research aims to focus on biomedical applications, specifically to obtain strong adhesion of the implant material layer, which is expected to improve osseointegration and reduce inflammation effects from implantation. The research method is experimental (testing), using both qualitative and quantitative methods. The coating method used is the Dip Coating method. Research variables include variations in the weight percentage (wt%) of PVA+ZrO2, and HA suspension, as well as variations in sintering temperatures, 800, 900 dan 9500C. The study results showed that the addition of Polyvinyl Alcohol (PVA) and Zirconium Oxide (ZrO2) in the suspension can reduce cracks on the test specimen layer. Optimal results were obtained with the addition of 20% PVA and ZrO2 weight at a sintering temperature of 900Â°C. The implant material surface was uniformly coated, and no cracks were found.